2022
DOI: 10.1186/s12879-022-07144-5
|View full text |Cite
|
Sign up to set email alerts
|

High procalcitonin levels associated with increased intensive care unit admission and mortality in patients with a COVID-19 infection in the emergency department

Abstract: Background Patients with a severe COVID-19 infection often require admission at an intensive care unit (ICU) when they develop acute respiratory distress syndrome (ARDS). Hyperinflammation plays an important role in the development of ARDS in COVID-19. Procalcitonin (PCT) is a biomarker which may be a predictor of hyperinflammation. When patients with COVID-19 are in the emergency department (ED), elevated PCT levels could be associated with severe COVID-19 infections. The goal of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 30 publications
7
27
1
1
Order By: Relevance
“…It was an independent risk factor for ICU admission (OR: 1.492, 95% CI: 1.031-2.160) in the multivariate analysis. Similar to our study, Tong-Minh et al (24) showed correlation between procalcitonin levels and mortality and procalcitonin was an independent risk factor for mortality (OR: 2.11, 95% CI: 1.36-3.61) in multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…It was an independent risk factor for ICU admission (OR: 1.492, 95% CI: 1.031-2.160) in the multivariate analysis. Similar to our study, Tong-Minh et al (24) showed correlation between procalcitonin levels and mortality and procalcitonin was an independent risk factor for mortality (OR: 2.11, 95% CI: 1.36-3.61) in multivariate analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have shown that some routine clinical laboratory tests, such as lymphocyte count, lactate dehydrogenase and D-dimer are known to be affected in patients with COVID-19 (20), with lymphopenia, raised lactate dehydrogenase and elevated D-dimer being associated with worse disease severity and outcomes (21-23). Other studies have shown significant differences in inflammatory markers amongst patients who required ICU admission compared to patients who have not, and markers of infection and inflammation such as C-reactive protein, procalcitonin, and ferritin which are, as expected, correlated with severe disease (24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 67%
“…However, since treatments used for COVID-19 can alter the classical inflammation markers, detecting a bacterial infection in the earlier phase of the pandemic was more difficult [ 6 ]. In addition, COVID-19 itself increases C-reactive protein (CRP) and procalcitonin values—markers for bacterial infection, whose values are associated with disease severity [ 7 ].…”
Section: Introductionmentioning
confidence: 99%